Volumetric Modulated Arc Therapy Technique In Cases Of Tongue Cancer In Radiation Oncology Installation MRCCC Siloam - bani, ismil (Journal of Applied Health Management and Technology, 2022)
ABSTRAKÂ The development of radiotherapy techniques keeps growing, which one is the technique of irradiation of Volumetric Modulated Arc Therapy. At Radiation Oncology Instalation MRCCC Siloam Semanggi, in the case of tongue cancer iradiation using Volumetric Modulated Arc Therapy technique. The objective of this research is to describe the procedure of Volumetric Modulated Arc Therapy technique in the cases of tongue cancer at Radiation Oncology Instalation MRCCC Siloam Semanggi. The design of this study is descriptive with one sample primary in the case of tongue cancer with Volumetric Modulated Are Therapy technique. The research methods are conducted by the study literature, observation, interview, and documentation. This research was conducted at Radiation Oncology Instalation MRCCC Siloam Semanggi Hospital April to May 2022. The results of this research can be concluded that the procedure of Volumetric Modulated Arc Therapy technique in the cases of tongue cancer at Radiation Oncology Instalation MRCCC Siloam Semanggi covers the description of the procedures of patient preparation. preparation of tools and materials used during the process of irradiation, the iradiation CT simulation process in CT-Simulator, iradiation planning process at the Treatment Planning System (TPS). He verification process of irradiation with On-Board Imnager (OBI) and last process ofiradiation of the patient with Linac.